Cholesterol in the Cell Membrane-An Emerging Player in Atherogenesis - Paukner, Karel; Králová Lesná, Ivana; Poledne, Rudolf (International journal of molecular sciences, 2022)
Membrane cholesterol is essential for cell membrane properties, just as serum cholesterol is important for the transport of molecules between organs. This review focuses on cholesterol transport between lipoproteins and lipid rafts on the surface of macrophages. Recent studies exploring this mechanism and recognition of the central dogma-the key role of macrophages in cardiovascular disease-have led to the notion that this transport mechanism plays a major role in the pathogenesis of atherosclerosis. The exact molecular mechanism of this transport remains unclear. Future research will improve our understanding of the molecular and cellular bases of lipid raft-associated cholesterol transport.
Keywords: zvířata; macrophages; Cell Membrane; membránové mikrodomény; Atherosclerosis; buněčná membrána; cholesterol; Humans; Protein Binding; lipoproteiny; Lipid Metabolism; Biological Transport; makrofágy; lidé; ateroskleróza; Cholesterol; Animals; cell membrane; homeostáza; Membrane Microdomains; biologický transport; Lipoproteins; Homeostasis; metabolismus lipidů; vazba proteinů; Macrophages